A Magellanic origin for the Virgo sub-structure - Boubert, D; Belokurov, V; Erkal, D; Iorio, G (Oxford University Press, 2018)
The Milky Way halo has been mapped out in recent work using a sample of RR Lyrae stars drawn from a cross-match of Gaia with 2MASS. We investigate the significant residual in this map which we constrain to lie at Galactocentric radii 12 < R < 27 kpc and extend over 2600 deg2 of the sky. A counterpart of this structure exists in both the Catalina Real Time Survey and the sample of RR Lyrae variables identified in Pan-STARRS, demonstrating that this structure is not caused by the spatial inhomogeneity of Gaia. The structure is likely the Virgo Stellar Stream and/or Virgo Over-Density. We show the structure is aligned with the Magellanic Stream and suggest that it is either debris from a disrupted dwarf galaxy that was a member of the Vast Polar Structure or that it is SMC debris from a tidal interaction of the SMC and LMC 3 Gyr ago. If the latter then the sub-structure in Virgo may have a Magellanic origin.